Hypothermia Intervention In Newborn With Early Breastfeeding Initiation - Alfiyah Dwi Rahmawati; Eny Sendra; Triatmi Andri Yanuarini; Ririn Indriani (Indonesian Journal of Applied and Industrial Sciences (ESA), 2023)
Hypothermia is a baby’a body temperature below normal. Low temperatures cause metabolic and physiological processes to occur more slowly. The purpose of this study was to determine interventions for newborns, with hypothermia.  Types and methods uses literature review. A search from the Google Scholar dabase for a number of registered journals and having a DOI (Digital Object Identifier) and ISSN (International Standard Serial Number). Journals were selected for the last 5 years (2015-2020), with the topic of newborn intervention with hypothermia. The analysis technique stars from the initial research year and gradually extends to the old year. Conclusion : hypothermia intervention in newborna with breastfeeding initiation for 1 hour can increase the newborn’s body temperature by 1-2°C. It si hoped that midwives will be able to provide delivery care for newborns with breastfeeding initiation in the first hour to prevent hypothermia.